Dirty John [videorecording (DVD)] - Britton, Connie; Bana, Eric; Temple, Juno, 1989-; Garner, Julia, 1994- (Universal Pictures Home Entertainment, 2019)
Debra Newell has a seemingly perfect life: she's successful, beautiful and lives in one of California's most desirable coastal cities. Newport Beach. The only thing missing is love. So when she finally meets charming and handsome doctor John Meehan she's quickly swept into a whirlwind romance, much to the dismay of her daughters Terra and Veronica.